Transformasi Digital Usaha Kecil Penjualan Kerupuk Moro dengan Metode Agile - Zulfachmi Zulfachmi; Rena Amalia Hasibuan; Anggraini Eka Saputri (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
Indonesia is a capture fisheries country that has a major role in capture fisheries production in the world. Indonesia itself includes a lot in producing fisheries and consuming fish. The industrialization of fishery products is very important, through socio-economic and cultural transformation of fisheries that can change the search system of an agrarian society into an industrial society. So that the industrialization of fisheries is not just a part of fish processing, but also development and production activities, both catching and cultivating which can produce goods that are able to meet human needs. One of the small industrial businesses in the field of mackerel processing is the manufacture of moro crackers. There is a problem with this small industrial business, the product of moro crackers is not widely known or reached by tourists. Therefore the author wants to expand the product so that it is better known by the wider community and tourists, so that moro crackers can become an icon for Moro Regency, and to increase production so that these moro crackers can compete in foreign markets. In this small industrial business, Moro crackers have several shortcomings in terms of product promotion and service efficiency to consumers. To improve these deficiencies, we need a system that can help in terms of promotion and fast service to consumers. Therefore, an e-commerce website is proposed using the aglie method which is expected to help small businesses promote products online and offline and consumers and businesses can carry out sales activities in it.